Mulheres e maternidade tardia: por que agora? - Lima, Marina Simas de (2012)
The aim of this study was to understand late motherhood experienced by contemporary women aged over 40 years, its biological time, its meanings and its implications from a systemic perspective. The methodology chosen was the qualitative research with case study design. The two participants were 40 to 45 year-old working women with college degree. The instruments used were, among others: timeline, genogram and interview focused on maternity as a means to deepen the investigation. The study was based on the material produced to try to understand what is common or specific among these women on the threshold of their biological time to reach the goal of maternity. The research results were interpreted in light of the systemic view, in which both the observer and the observed take part in the process. According to this approach, any observer includes himself/herself in the observation he or she makes. The following thematic categories emerged: influence of the family of origin, parental and maternal models, beliefs in the family s traditions and the woman s position, importance given to living conditions to get pregnant, chronological time, chronological age versus maturity, profit obtained through maternity, network obtained through maternity, career, financial support, abortion, mother s role, paradoxical needs, remarriage and role balance. In the last considerations, important issues are found such as the women s need to be aware of their own wishes and values in order to make their choice by creating strategies in search of their goals, according to their priorities and biological time, and better understanding the dilemmas of today s women